Analysis of Validation Results of Electronic Student Worksheet Based on Multi Representation of Linear Motion Kinematics Materials - Lia Apriliana; Ismet Ismet; Ida Sriyanti (Universitas Lambung Mangkurat, 2022)
Multi-representation-based electronic student worksheets are learning media with teaching materials that include verbal components, pictures, graphics, and mathematics. This study aimed to analyze the electronic student worksheet based on multi-representing valid linear motion kinematics material in high school physics class X. The research was conducted using Define-Design-Develop-Disseminate) model. Produce a valid product. There are two main aspects that we will analyze, namely: material and media. The results of the validation of the material aspects with indicators (1) content/breadth of material include material breadth, material depth, material truth, material completeness, material presentation, learning evaluation, and student activities with a percentage of 79% (valid), (2) Presentation of material that are covering techniques for presenting material, systematics, and generating motivation to learn with a percentage of 80% (valid), and (3) Language which includes sentence clarity, conformity with Indonesian language rules, and very valid status sentence structure with a percentage of 80% (valid). Meanwhile, the results of the analysis for the validation of media aspects with indicators (1) Didactic, which includes the learning process and ability development with a percentage of 80% (valid), (2) Construction which includes the accuracy of using language and sentences, paying attention to students' abilities, and has benefits, objectives, and identity with a percentage of 97% (very valid), and (3) Technical, said to be very valid by media experts on all indicators with a percentage between 97% (very valid). Based on the results of the analysis of the electronic student worksheet based on multiple representations, the media developed is valid. This media can analyze problem-solving skills in high school physics learning. This research is expected to reference other researchers in developing physics learning media.